NMDA-receptor encephalitis: An unsual case of refractory status epilepticus. (3rd June 2015) - Lapointe, S; Legault, C; Giacomini, P; La Piana, R; Teitelbaum, J; Tampieri, D; Romano, A
Abstract : Objective: Case report of NMDA receptor encephalitis in a young man with early refractory status epilepticus and atypical radiological findings. Background: Anti-NMDA receptor encephalitis is an autoimmune disorder due to antibodies to the NR1-NR2B heterodimer of NMDA receptor. On imaging, it typically presents with T2 hyperintensities in mesio-temporal lobes, cerebral cortex and basal ganglia. We present a case with a dramatic clinical evolution and novel imaging findings. Design/ Methods: Case report and review of imaging. Results: 29-year-old male presented with mood disturbance followed by partial-complex seizures, facial dyskinesia and choreo-athetotic movements. Initial MRI showed subtle T2-hyperintensities in mesio-temporal lobes. Diagnosis of NMDA-receptor encephalitis was confirmed after CSF antibody detection. Prior to diagnostic confirmation, he developed refractory status epilepticus, and concomitant signs of herniation. A repeated MRI showed increased T2-hyperintensities of thalami and mesencephalon, with cerebellar involvement and transtentorial/foraminal herniation. Restricted diffusion was documented in the cerebellar cortex/thalami/putamina and caudate. IV corticosteroids and hypertonic fluid reversed herniation, and halted the seizures. Conclusions: To our knoweldge, we report the first case report of uncal and tonsillar herniation in NMDA-r encephalitis secondary to atypical, predominant cerebellar involvement. This case highlights life-threatening manifestation that physicians might encounter, and a possible role for high dose IV corticosteroids as an adjunct treatment for brain edema and seizures.